The integrity of the infant in the curriculum - Esparza Hernández, Sandra Liliana; Mantilla Quintero, Zulima Yolima; Patiño Olachica, Luz Amparo (Rastros Rostros, 2002)
In order to contribute to the integral development of the child, a new curriculum design is required whose purpose is to provide guidance based on physical, psychological, moral, affective, sensitive and creative formation, achieving a well-defined personality, with the capacity to discover new realities and the possibility of living in a better world. The educational system governed by the General Law of Education 115 establishes school autonomy in educational institutions to design a curriculum that meets the particular needs of the establishment and at the same time allows the student to develop all their potentialities, skills and abilities favoring their integrity